Effect of Conjugated Hyperbilirubinemia on the Prognosis of Patients Hospitalized in Intensive Care Unit at Kariadi Hospital Semarang - Agung Prasetyo; Djallalluddin Djallalluddin; Hirlan Hirlan; Agus Suryanto (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: In critically-ill patients, liver dysfunction plays a significant role on patient’s morbidity and mortality in the intensive care unit (ICU). Metabolic, hemodynamic and inflammatory factors also contribute in liver damage. Bilirubin is one of clinical markers for liver dysfunction. Some literatures indicated that patients with hyperbilirubinemia have higher mortality rate. The aim of this study was to assess the death prognosis of critically-ill patients with hyperbilirubinemia. Method: This study was an observational, prospective, and cohort study. All patients at the ICU of Kariadi hospital with hyperbilirubinemia were consecutively recruited over 8-month period from May 1st 2008 to January 31st 2009. Hyperbilirubinemia was defined as serum bilirubin levels ≥ 1.3 mg/dL for at least 72 hours and no hyperbilirubinemia was observed when the patients were admitted to the hospital. Results: Of 79 subjects who fulfilled inclusion criteria, the incidence of hyperbilirubinemia in critically-ill patients was 39.2%. About 56 subjects were enrolled in the study. Among them, 28 subjects showed hyperbilirubinemia and the other 28 subjects were included in the control group. There was no significant difference regarding the baseline characteristics of hyperbilirubinemia group and non- hyperbilirubinemia group. At the end of the study, the mortality rate in hyperbilirubinemia patients were 60.7% and 21.3% in the non-hyperbilirubinemia patients. The relative risk (RR) of death was 2.8; (95% CI = 1.3 - 6.1; p = 0.003). Conclusion: The incidence of hyperbilirubinemia was high in critically ill-patients hospitalized in the ICU of Kariadi hospital. The incidence of death between non-hyperbilirubinemia and hyperbilirubinemia subjects was significantly different. The significant relative risk of death indicates that hyperbilirubinemia may have influences on the mortality rate of critically-ill patients hospitalized in the ICU.   Keywords: liver dysfunction, hyperbilirubinemia, death